Trends and risk factors of global incidence, mortality, and disability of genitourinary cancers from 1990 to 2019: Systematic analysis for the Global Burden of Disease Study 2019 - Tian, Yi-Qun; Yang, Jin-Cui; Hu, Jun-Jie; Ding, Rong; Ye, Da-Wei; Shang, Ji-Wen (Frontiers in Public Health, 2023)
Background The incidence of kidney, bladder, and prostate cancer ranked ninth, sixth, and third in male cancers respectively, meanwhile, the incidence of testicular cancer also increased gradually in the past 30 years. Objective To study and present estimates of the incidence, mortality, and disability of kidney, bladder, prostate, and testicular cancer by location and age from 1990 to 2019 and reveal the mortality risk factors of them. Materials The Global Burden of Diseases Study 2019 was used to obtain data for this research. The prediction of cancer mortality and incidence was based on mortality-to-incidence ratios (MIRs). The MIR data was processed by logistic regression and adjusted by Gaussian process regression. The association between the socio-demographic index and the incidence or disease burden was determined by Spearman's rank order correlation. Results Globally in 2019, there were 371,700 kidney cancer cases with an age-standardized incidence rate (ASIR) of 4.6 per 100,000, 524,300 bladder cancer cases, with an ASIR of 6.5 per 100,000, 1,410,500 prostate cancer cases with an ASIR of 4.6 per 100,000 and 109,300 testicular cancer incident cases with an ASIR of 1.4 per 100,000, the ASIR of these four cancers increased by 29.1, 4, 22, and 45.5% respectively. The incidence rate of the four cancers and the burden of kidney cancer were positively correlated with the socio-demographic index (SDI), regions with a higher SDI faced more of a burden attributable to these four cancers. High body-mass index has surpassed smoking to be the leading risk factor in the past thirty years for kidney cancer mortality. Smoking remained the leading risk factor for cancer-related mortality for bladder cancer and prostate cancer and the only risk factor for prostate cancer. However, the contribution of high fasting plasma glucose to bladder cancer mortality has been increasing. Conclusion The incidence of bladder, kidney, prostate, and testicular cancer is ever-increasing. High-income regions face a greater burden attributable to the four cancers. In addition to smoking, metabolic risk factors may need more attention.